2017
DOI: 10.3390/su9030443
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Change of Vegetation Cover and Associated Driving Forces in Nanxiong Basin, China

Abstract: Natural climate change and human activities are the main driving forces associated with vegetation coverage change. Nanxiong Basin is a key ecosystem-service area at the national level with a dense population and highly representative of red-bed basins, which are considered as fragile ecological units in humid regions. In this study, the authors aimed to determine the trends in vegetation cover change over past two decades and the associated driving forces in this study area. The Normalized Difference Vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…The experimental site is located in Nanxiong Basin, which is a typical red-bed basin with a severe soil erosion problem due to its dominant purple soil texture (Calcaric Regosols in FAO taxonomy), fragile ecological environment, severe soil erosion, and the fact that red clay-rich sediments of the parent rock are mainly distributed in the central part of the basin. It has an elevation of 48-1421 m above sea level [44] with a moist, subtropical monsoon climate, and four distinct seasons, including a long summer and short winter, and a fast autumn transition. Average temperature is 19.6ºC, maximum temperature is 39.6ºC, and the extreme minimum temperature is -6.2ºC.…”
Section: Experimental Sitementioning
confidence: 99%
“…The experimental site is located in Nanxiong Basin, which is a typical red-bed basin with a severe soil erosion problem due to its dominant purple soil texture (Calcaric Regosols in FAO taxonomy), fragile ecological environment, severe soil erosion, and the fact that red clay-rich sediments of the parent rock are mainly distributed in the central part of the basin. It has an elevation of 48-1421 m above sea level [44] with a moist, subtropical monsoon climate, and four distinct seasons, including a long summer and short winter, and a fast autumn transition. Average temperature is 19.6ºC, maximum temperature is 39.6ºC, and the extreme minimum temperature is -6.2ºC.…”
Section: Experimental Sitementioning
confidence: 99%
“…Moreover, because of the interdisciplinary perspective that is created by having several sub-disciplinary fields within physical geography, including geomorphologists, climatologists, soil scientists, biogeographers, and hydrologists, it is possible to include a breadth of research studies and expertise that stretches beyond most environmental disciplines. The papers in this Special Issue, for instance, have entailed soil science (e.g., [4,6]) as well as landscape change (e.g., [3,9]) and impacts due to climate change, including flooding (e.g., [10,11]). A variety of methodological approaches are incorporated here, with spatial technology (remote sensing, GIS, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…A variety of methodological approaches are incorporated here, with spatial technology (remote sensing, GIS, etc.) included in several studies (e.g., [1][2][3][4]), serving to portray the role of technology on data compilation and analysis in geographical research. Data visualization is evident in paper [11] for modelling and, earlier in the Special Issue, [1] explores data-sharing based on data acquired from Earth observation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies 67 have shown that the purple soil formed on redbed parent material is the most seriously eroded of all soil 68 types in the Yangtze River Basin. This is especially visible in humid regions, where severe erosion can 69 threaten the eco-security (Yan et al, 2017). The change in soil structure and the removal of topsoil 70 resulting from the erosion may cause nutrient removal and environmental degradation, thereby inhibiting 71 plant growth (Sheoran, Sheoran, & Poonia, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A subtropical monsoon climate prevails, with long hot summers and 85 short winters. The average temperature is 19.6 ℃ and the annual precipitation and evaporation are 1555.1 86 mm and 1678.7 mm, respectively (Yan et al, 2017). The total area of Nanxiong Basin is 3692 km 2 .…”
mentioning
confidence: 99%